Estimation Of Fetal Weight Using The Risanto Formula And The Johnson-Thausack Formula Compared To Birth Weight - Risyanti, Berty; Julaeha, Nita Elita (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Latar Belakang: bagian penting dari asuhan kebidanan adalah mengukur tinggi fundus uteri untuk memastikan perkiraan berat badan bayi. Pengetahuan mengenai perkiraan berat badan janin memungkinkan bidan, untuk mengantisipasi potensi masalah dan menyusun strategi untuk mengatasinyaTujuan: mengetahui perbedaan akurasi antara Rumus Risanto dan Rumus Jhonson Thausack dalam menentukan taksiran berat janin di RS Ibu dan Anak Al Islam BandungMetode: Desain Penelitian ini adalah Cross Sectional Design, Populasi adalah ibu inpartu kala 1 fase laten yang melahirkan di RS Ibu dan Anak Al Islam periode Mei – Juni 2024 sebanyak 61 orang. Teknik pengambilan sampel menggunakan Total Sampling.Hasil: Terdapat perbedaan yang signifikan antara berat bayi lahir dengan TBJ Risanto (p=0,001) dan berat bayi lahir dengan TBJ Johnson Tohsack (p=0,001). Dari uji yang membandingkan akurasi antara rumus Risanto dan rumus Johnson Thausack didapatkan hasil rata- rata untuk TBJ Risanto sebesar 2824,92 gram dan TBJ Johnson Tohsack sebesar 2614,67 gram, dan sementara berat bayi yang dilahirkan adalah 3084,02 gram.Kesimpulan: Terdapat perbedaan yang signifikan secara statistik antara rumus Risanto dan Johnson Thausack dengan berat bayi lahir yang sebenarnya, rumus Risanto lebih mendekati dengan berat bayi lahir.Saran: Bidan lebih meningkatkan ketelitian dalam pengukuran TFU dan menggunakan rumus Risanto untuk mengukur TBJ sehingga hasil pengukuran dapat digunakan dalam pelayanan kebidanan. Kata Kunci : Taksiran berat Janin, Rumus Risanto, Rumus Johnson Thausack ABSTRACT Background: A crucial aspect of midwifery practice involves assessing the height of the uterine fundus to determine the estimated fetal weight. Understanding this estimated weight enables the midwife to foresee possible complications and develop appropriate strategies to address them.Objective: to evaluate the accuracy disparity between the Risanto Formula and the Johnson Thausack Formula in estimating fetal weight at Al Islam Mother and Child Hospital in Bandung.Methods: This study employs a Cross-Sectional Design, focusing on a population of 61 mothers in the latent phase of the first stage of labor who delivered at Al Islam Mother and Child Hospital between May and June 2024. The sampling method utilized was total sampling.Results: A notable difference was observed between the birth weight of babies estimated using the Risanto formula (p=0.001) and those estimated using the Johnson Tohsack formula (p=0.001). When comparing the accuracy of these two formulas, the average estimated fetal weight (EFW) using the Risanto formula was 2824.92 grams, while the Johnson Tohsack formula yielded an average EFW of 2614.67 grams. In contrast, the actual average birth weight of the newborns was 3084.02 grams.Conclusion: A statistically significant difference exists between the Risanto and Johnson Thausack formulas when compared to the actual birth weight, with the Risanto formula providing an estimate that is more closely aligned with the actual birth weight.Suggestion: Midwives should enhance the precision of fundal height measurements and apply the Risanto formula to estimate fetal weight, ensuring that the results are reliable for use in midwifery care. Keywords: Estimated Fetal Weight, Risanto Formula, Johnson Thausack Formula